Plasmid-mediated resistance to tetracyclines among Neisseria gonorrhoeae strains isolated in Poland between 2012 and 2013 - Młynarczyk-Bonikowska, Beata; Kujawa, Marlena; Malejczyk, Magdalena; Młynarczyk, Grażyna; Majewski, Sławomir (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction: One of two main mechanisms of resistance in tetracycline-resistant Neisseria gonorrhoeae (TRNG) is associated with the presence of TetM protein responsible for actively blocking of the tetracycline target site in the 30S ribosomal subunit. This mechanism is encoded by conjugative plasmids. The second mechanism is chromosomal in nature and due to mutations in specific genes. Aim: To determine the incidence and type of tetM determinants in TRNG strains isolated from patients presenting with gonorrhea infection to the Dermatology and Venereology Clinic in Warsaw in 2012–2013. Material and methods : Tetracycline and doxycycline susceptibility was determined by E-Tests. The presence and type of the tetM gene were determined by polymerase chain reaction. Results : Tetracycline resistance was detected in 50.8% of the evaluated strains. The TRNG strains containing the tetM plasmid constituted 13.8% of all the evaluated strains. Dutch type tetM constituted 12.3% and American type tetM 1.5% of all the evaluated strains. In the remaining TRNG strains, resistance to tetracyclines was presumably chromosome-encoded. The minimal inhibitory concentration (MIC) of tetracycline ranged from 0.25 to 32.0 mg/l, MIC 50 = 2.0 mg/l, MIC 90 = 32.0 mg/l. The MIC of doxycycline ranged from 0.25 to 32.0 mg/l, MIC 50 = 4.0 mg/l, MIC 90 = 16.0 mg/l. Conclusions : Unlike most of European countries, in 2012–2013 in Poland, the Dutch type tetM was found to be much more common than the American type. Minimal inhibitory concentration values of tetracycline and doxycycline were similar, with doxycycline exhibiting a somewhat lower effectiveness in vitro than tetracycline towards chromosome-mediated tetracycline resistant strains of N. gonorrhoeae .